2016
DOI: 10.22146/ijbiotech.15273
|View full text |Cite
|
Sign up to set email alerts
|

An Active of Extracellular Cellulose Degrading Enzyme from Termite Bacterial Endosimbiont

Abstract: Cellulase is an ezyme that specifi cally cleaves the 1,4-β-glycosidic bond of cellulose to produce the small fragments of simple carbohydrate. This work was aimed to characterize the extracellular cellulase from Paenibacillus spp., which was previously isolated from macro termites, Odontotermes bhagwatii in our laboratory. Two Paenibacillus isolates were used in this experiment, namely Paenibacillus cellulositrophicus SBT1 and Paenibacillus, sp. SBT8. Analysis of the total proteins in the supernatants showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The five bacterial isolates composing the consortium presented different patterns of substrate utilisation and were able to use lipids as growth support, especially fatty acid esters, as well as amino acid derivates, which reflects their metabolic potential and could confer an advantage in terms of both adaptation and biodegradation efficiency. Previous studies have explored the ability to produce aliphatic and aromatic hydrocarbon-degrading enzymes by the bacterial species conforming the consortium, e.g., hemicellulase, exoglycanases, xylanases, and laccases from Cellulosimicrobium cellulans (Wang et al 2018 ), alkane and cytochrome P450 monooxygenases, ring-hydroxylating dioxygenases, laccases and dehalogenases from Rhodococcus corynebacteroides (Chukwuma et al 2021 ) and Rhodococcus qingshengii (Lincoln et al 2015 ), ligninase and cellulase from Paenibacillus cellulositrophicus (Rohman et al 2015 ), and alkane hydroxylase and laccase from Stutzerimonas stutzeri (Parthipan et al 2017 ). The results presented here showed that Stutzerimonas stutzeri PH5 is also capable of using aliphatic sulphur compounds (aliphatic thiols and mercaptans) and potentially other reduced sulphur-containing compounds as a source of energy, which have been identified as linking structures in asphaltene and resin alkyl bridges (Bava et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The five bacterial isolates composing the consortium presented different patterns of substrate utilisation and were able to use lipids as growth support, especially fatty acid esters, as well as amino acid derivates, which reflects their metabolic potential and could confer an advantage in terms of both adaptation and biodegradation efficiency. Previous studies have explored the ability to produce aliphatic and aromatic hydrocarbon-degrading enzymes by the bacterial species conforming the consortium, e.g., hemicellulase, exoglycanases, xylanases, and laccases from Cellulosimicrobium cellulans (Wang et al 2018 ), alkane and cytochrome P450 monooxygenases, ring-hydroxylating dioxygenases, laccases and dehalogenases from Rhodococcus corynebacteroides (Chukwuma et al 2021 ) and Rhodococcus qingshengii (Lincoln et al 2015 ), ligninase and cellulase from Paenibacillus cellulositrophicus (Rohman et al 2015 ), and alkane hydroxylase and laccase from Stutzerimonas stutzeri (Parthipan et al 2017 ). The results presented here showed that Stutzerimonas stutzeri PH5 is also capable of using aliphatic sulphur compounds (aliphatic thiols and mercaptans) and potentially other reduced sulphur-containing compounds as a source of energy, which have been identified as linking structures in asphaltene and resin alkyl bridges (Bava et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of thermolysin, a kind of metalloprotease, it stoichiometrically contained 1gatom of Zn and 4 gatom of Ca per enzyme molecule (Tsuru et al, 1966). Previously, we have reported that the extracellular cellulase preferred Mg 2+ and Zn 2+ for enzymatic activity, since both have similar ionic radii (Rohman et al, 2015). It is apparently that the preference of ligand binding formation is more important for structure stability of the proteins, instead for enzymatic reaction.…”
Section: Effect Of Divalent Metal Ions On the Enzymatic Activity Of Cmentioning
confidence: 95%
“…To overcome the weaknesses of that research, rice bran tempeh can be enriched with cellulase. Cellulase reduces levels of crude fiber, such as cellulose in feed ingredients (Rohman et al, 2015). Cellulases are able to hydrolyze cell walls (Holland et al, 2020;Jamet and Dunand, 2020;Camacho-Fernández et al, 2021).…”
Section: Introductionmentioning
confidence: 99%